2011
DOI: 10.1016/j.annemergmed.2010.07.001
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Incremental Value of the ABCD2 Score in the Emergency Department Evaluation of Transient Ischemic Attack

Abstract: Objective To study the incremental value of the ABCD2 score in predicting short term risk of ischemic stroke following thorough ED evaluation of transient ischemic attack (TIA). Methods This was a prospective observational study of consecutive patients presenting to the Emergency Department (ED) with a TIA. Patient underwent a full ED evaluation including CNS and carotid artery imaging, after which ABCD2 scores and risk category were assigned. We evaluated correlations between risk categories and occurrence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…Eleven were population-based studies including cohorts from the UK (Oxford), Ireland (Dublin), USA (Texas and Minnesota), Canada (Alberta) and northern Portugal. 9 23,127,129,131,135,136,143,149,153,159 and by both in four; 62,158,162,163 in three studies 120,138,155 this information was not reported.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 85%
See 3 more Smart Citations
“…Eleven were population-based studies including cohorts from the UK (Oxford), Ireland (Dublin), USA (Texas and Minnesota), Canada (Alberta) and northern Portugal. 9 23,127,129,131,135,136,143,149,153,159 and by both in four; 62,158,162,163 in three studies 120,138,155 this information was not reported.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 85%
“…178 To reduce the impact of any between-study heterogeneity, we considered separately the 10 studies that provided data on stroke risk at both 7 and 90 days. 62,137,139,143,[149][150][151][152]158,163 The study by Asimos and colleagues was published in two reports. 136,143 Even although the same cohort of patients was studied in both publications, data on risk of stroke at 7 days were reported in the 2010 publication, whereas data on risk of stroke at 90 days were reported in the 2009 publication.…”
Section: Main Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…The low risk of stroke development from TIA in our study could be due to the fact that the majority of patients received early treatment with anti-platelets/anticoagulation and vascular risk factor control 14 . In fact, medical literature shows that the lowest risks were seen in emergency department studies and the highest risks were seen in population-based studies without urgent treatment (0.9% vs 11%) at 7 days after admission to the hospital 15 .…”
mentioning
confidence: 99%